Juegos motrices para desarrollar la capacidad de reacción a los niños de la Escuela Formativa Cooperativa San Juan - Caballero Santana, Jesús Daniel (2023)
This present project exposes and is born from the need to know the motor games to develop the ability to react to children, with the aim of determining how the implementation of motor games influences the development of the ability to react to Children of the Cooperative Training School. San Juan; Therefore, to begin with, the theoretical framework was carried out, where the general and necessary data to carry out the investigation were covered, where various topics were highlighted, taking into account that the game is part of the daily life of children from the earliest years. after birth, and spend a lot of time playing, which develops aspects such as socialization, growth, personal development and the ability to react in areas such as: cognitive, emotional, intellectual, physical and social. Motor development and stimulation are important at an early age because they contribute to motor skills and the child's ability to react in their activities focused on physical and functional development through the maturation of the nervous system that occurs through motor games. in different areas and fields. To find out how motor games develop reaction capacity, a research methodology has been used with a non-experimental modality and with a type of descriptive and explanatory research; In addition, I have implemented techniques such as observation and instruments such as surveys in order to compile the main theoretical bases that support the game as psychomotor development strategies and establish the strategies used by teachers to encourage children to participate in recreational activities and to locate, identify the relevant information for the investigation in order to reach a conclusion in this project.